Bio-based 3D dendritic silica nanosphere: A green superior adsorbent. (10th February 2022) - Soltani, Roozbeh; Nazari, Marziyeh; Marjani, Azam; Faisal, Muhammad; Pirestani, Niloofar; Albadarin, Ahmad B.; Soltani, Soroosh; Su, Chia-Hung; Chang, Che-Hao; Pishnamazi, Mahboubeh; Ansari, Mohammad Javed; Shirazian, Saeed
Abstract: The method of extracting silica from herbal resources is a new environmentally friendly approach to the preparation of nanoporous silica materials that involves lower costs compared to the conventional industrial method of extracting from natural quartz. Sedge ( Carex riparia ) is a widespread agricultural waste that grows naturally in many parts of the world. The extractable herbal amorphous silica in Sedge can makes it a good candidate as an alternative for current industrial resources of silica. Accordingly, for the first time, a novel kind of bio-based three-dimensional dendritic multi-organo-functionalized (amine, thiol, and carboxyl) silica nanospheres (denoted as 3D DMF-SNSs) with hierarchical bimodal micro-mesoporous channel structure and uniform monodispersed morphology has been successfully synthesized via an environmentally friendly approach. Due to their unique structural and morphological properties such as large surface area (601 m 2 g −1 ), high pore volume (0.99 cm 3 g −1 ), abundant active functional groups, and dendritic bimodal micro-mesoporous channels, 3D DMF-SNS nanoparticles show great potential for use as an adsorbent. Accordingly, in this work, systematic adsorption studies toward the simultaneous removal of chrysoidine G and thallium (I) by the 3D DMF-SNS from aqueous solutions were carried out. Isotherm, kinetic, thermodynamic, and adsorption-desorption investigations were performed and the calculated Langmuir maximum adsorption capacity of chrysoidine G and thallium (I) were calculated to be 880.6 mg g −1 and 806.7 mg g −1, respectively, under optimal conditions (pH = 7.0, adsorbent dose = 0.05 g L −1, contact time = 14 min for chrysoidine G and 20 min for thallium (I), solution temperature = 293 K). Regeneration studies were carried out in ten consecutive adsorption-desorption cycles at 293 K and it was found that the experimental adsorption capacities for chrysoidine G and thallium (I) were decreased to 745 and 660 mg g −1, respectively, indicating the stability of the adsorbent and its excellent adsorption performance even after using it in ten consecutive cycles for simultaneous adsorption of the adsorbates. Graphical abstract: Image 1 Highlights: Bio-based 3D DMF-SNS was synthesized using a simple and effective synthesis protocol. Sedge was used as an environmentally friendly silica source in the synthesis method. 3D DMF-SNS was used as an adsorbent for the removal of chrysoidine G (CG) and Tl(I). The adsorption capacities of CG and Tl(I) were 880.6 and 806.7 mg g −1 . This adsorbent is advantageous for simultaneous high-efficient adsorption of CG and Tl(I).